THE EDUCATIONAL MANAGEMENT ROLE IN THE CURRENT SOCIAL - ECONOMIC CONTEXT - ANCA JARMILA GUŢĂ; MARTA-MIHAELA CHIŞ (Annals of the University of Petrosani: Economics)
This paper aims to clarify the place that it occupies in the management of educational management as a science and the current social -economic context. The importance of integrating the educational management in the pedagogical concerns interdisciplinary consists of the meeting between the general area of social and human sciences at the economics and those of education. The paper summarizes the principles and functions of this field of science from the perspective of the main researchers in this field related to education issues specified in the law.